1999
DOI: 10.1021/jf9813079
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Study of Changes in Fish Actomyosin during Setting

Abstract: Actomyosins (AMs) isolated from tilapia, lemon sole, ling cod, and rock fish were heated at 40 degrees C, and structural changes in AMs were investigated using Raman spectroscopy to elucidate low-temperature gelling phenomenon, that is, "setting", of surimi. The following conformational transitions were observed in lemon sole, ling cod, and rock fish gels during setting: a slow unfolding of alpha-helix and exposure of hydrophobic amino acid residues occurring in long-time incubation at 40 degrees C, thereby fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…AM was extracted using a modified method to that described by Ogawa et al (1999). Fish or pork mince (100 g) was added 400 mL of 3.38 mM Na 2 HPO 4 -15.5 mM NaH 2 PO 4 buffer (pH 7.5) and homogenized for 2 min at <15°C.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…AM was extracted using a modified method to that described by Ogawa et al (1999). Fish or pork mince (100 g) was added 400 mL of 3.38 mM Na 2 HPO 4 -15.5 mM NaH 2 PO 4 buffer (pH 7.5) and homogenized for 2 min at <15°C.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The result was similar to that of Cofrades, Carechc, Carballo, and Jiménez Comenero (1993) who reported that viscosity decreased with higher ionic strength in both chicken and hacke AM. This was possibly due to the fact that an increase in salt concentration was accompanied by an increase in number of AM monomers, so that the smaller molecules resulted in smaller K values (Ogawa et al, 1999). Wakameda and Arai (1986) have demonstrated that myosin released upon incubation of carp myofibrils with 1.5-2.0 M KCl, which was the result of the selective detachment of F-actin by salt.…”
Section: Effect Of Temperature On Rheological Propertiesmentioning
confidence: 99%
“…186 A slow unfolding of a-helix, exposure of hydrophobic amino acids, and gauche-gauche-trans conformation of the disulfide bonds were observed during the low temperature (40°C) setting of actomyosins from various species of fish including lemon sole, ling cod and rock fish. 187 Actomyosin from tilapia, which did not form a gel by heating at 40°C, showed less unfolding of the helical structure, which was hypothesized as a prerequisite for gelation during setting. 187 Formation of formaldehyde in certain gadoid species has been suggested to play a role in the decreased solubility and altered texture of some fish after freezing or frozen storage.…”
Section: Handbook Of Vibrationalmentioning
confidence: 99%
“…187 Actomyosin from tilapia, which did not form a gel by heating at 40°C, showed less unfolding of the helical structure, which was hypothesized as a prerequisite for gelation during setting. 187 Formation of formaldehyde in certain gadoid species has been suggested to play a role in the decreased solubility and altered texture of some fish after freezing or frozen storage. Raman spectral analysis indicated a decrease in helical structure of cod myosin after treatment with 12 mM formaldehyde; involvement of hydrophobic interactions was also suggested by changes in the vibrational modes of aliphatic residues after addition of formaldehyde or frozen storage.…”
Section: Handbook Of Vibrationalmentioning
confidence: 99%
“…Actomyosin was extracted according to the method of Ogawa et al [11] with some modifications. After thawing at 4°C for 3-4 h, fish mince was centrifuged at 8,000 rpm for 10 min at 4°C, and the supernatant was discarded.…”
Section: Actomyosin Preparationmentioning
confidence: 99%